Research Agenda and Evolution of Digital Innovation—Visual Analysis based on CiteSpace - Shi, Yuting (Journal of Social Science and Humanities, 2025)
Nowadays, the research in the field of digital innovation is relatively rich and deepening, however, there is a lack of a systematic overview of the development and evolutionary trends of digital innovation. This paper uses CiteSpace software and combines bibliometric methods and scientific knowledge mapping to analyze the external characteristics, knowledge structure, hotspots and evolution of the literature on digital innovation, and clarifies the management connotation and research prospects of digital innovation, which has important theoretical significance for understanding the tendencies of global digital innovation. The findings are as follows: (1) The literature of digital innovation is formed with China, the United States and other countries as important power; (2) Hot themes can be summarized as Digital technology empowering industrial intelligence; The effect of corporate digital innovation; The process of corporate digital innovation; Digital innovation promoting economic sustainability; (3) Research of digital innovation initially focuses on the application and development of information technology. With the rise of a new generation of digital intelligence technology, research begins to concern digital technology to promote industrial intelligence; Then research concentrates on the effectiveness and process of enterprise digital innovation; In recent years, the social value of digital innovation has become a hot spot of research.